algebra 1

posted by .

Solve the Foll by substitution
x=1/5y
3x+2y=26

So, substitute 1/5y for x in the second equation. Then solve for y. Can you take it from here?

yes thanks I figured it out.
Danielle

  • algebra 1 -

    3x + 5y = _8

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
  2. ALGEBRA 1!PLZ HELP!

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back …
  3. math ALGEBRA

    Solve by graping the foll: A. 2X+Y=5 3X-Y=10 B.2X=Y+1 2X-Y=5 I don't know what "graping the foll" is, but problem #2 has no solution, because the lines Y = 2X -1 (from your fist equation) and Y = 2x -5 (from your second equation) never …
  4. How do I do this.?(Math.)

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second equation …
  5. substitution method

    -x-4y=-14 2x=y+1 Let's look at your two equations. -x - 4y = -14 2x = y + 1 Let's solve the second equation for y: y = 2x - 1 Now let's substitute (2x - 1) for y in the first equation: -x - 4(2x - 1) = -14 -x - 8x + 4 = -14 -9x + 4 …
  6. substitution method

    -3x+y=-5 x+2y=0 Your equations: -3x + y = -5 x + 2y = 0 Let's solve the second equation for x: x = -2y Now let's substitute -2y for x in the first equation to solve for y: -3(-2y) + y = -5 6y + y = -5 7y = -5 y = -5/7 Now let's substitute …
  7. algebra

    5x-2y=-5 y-5x=3 substitution Substitute 5x +3 for y in the first equation, then solve it for x. Substitute 5x +3 for y in the first equation, then solve it for x. When I subsitute 5x+3 into the equation I get x=1/5 and y=2 is this …
  8. algebra

    solve by substitution 3x-y = -7 x+y = -9 Substitute 3x+7 for y in the second equation, and solve the resulting equation for x.
  9. Algebra

    Please help to find x, y 1. 8x-y=17 6x+y=11 2. 5x-2y=17 2x+3y=3 Question no.1 8x-y=17 6x+y=11 (adding the equation) __________ (-y and +y will be 0) 14x =28 Taking variables to one side x=28 __ 14 14*2=28 therefore x=2 substitute this …
  10. Algebra 1

    What is an equation of a line perpendicular to the line with equation y = 1 - 3x a.y=-3x + 5 b. y=3x + 5 c.y=-1/3x + 5 d. y=1/3x + 5 To solve the linear system below, which substitution of unkowns is proper ?

More Similar Questions